Thermal Performance Curves of Functional Traits Aid Understanding of Thermally Induced Changes in Diatom-Mediated Biogeochemical Fluxes - Baker, Kirralee G.; Robinson, Charlotte M.; Radford, Dale T.; McInnes, Allison S.; Evenhuis, Christian; Doblin, Martina A. (Frontiers in Marine Science, 2016)
How the functional traits (FTs) of phytoplankton change with temperature is important for understanding the impacts of ocean warming on phytoplankton mediated biogeochemical fluxes. This study quantifies the thermal performance curves (TPCs) of FTs in the cosmopolitan model diatom, Thalassiosira pseudonana, to advance understanding of trade-offs between physiological (photoacclimation, carbon fixation, nitrate, phosphate and silicate uptake) and morphological traits (cell volume and frustule silicification). We show that each FT has substantial phenotypic plasticity and exhibits a unique TPC, varying in both shape and thermal optimum, and diverging from the growth response. The TPC for growth was symmetric with a thermal optimum (Topt) of 18 °C. In comparison, the TPC for primary productivity was warm-skewed with a Topt around 21 °C, whereas frustule silicification decreased linearly with increasing temperature. Together, this suggests that the optimal temperature for overall fitness is a balance of trade-offs in the underlying functional traits. Moreover, these results demonstrate that growth is not necessarily an accurate estimate of overall biogeochemical performance and that temperature change will likely influence elemental fluxes such as carbon and silicon. Finally, we show that temperature-driven changes in individual traits e.g. photoacclimation, can mimic responses experienced under other environmental stressors (high light) and so a multi-trait assessment is essential for accurate interpretation of the cellular impact of warming. This study also reveals that multi-trait analysis, in the context of TPCs, provides insight into the cellular physiology regulating the whole cell response and has the potential to provide better estimates of how diatom-mediated biogeochemical fluxes are likely to be impacted in the context of ocean warming. Analyzing the response of multiple traits more comprehensively over other environmental gradients may therefore provide a useful framework to advance understanding of how taxon-specific functional traits will respond to multifaceted ocean change.